ON A FAMILY OF POLYNOMIALS WITH RESPECT TO THE HAAR SYSTEM - Gogyan, S.L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
We construct a sequence of polynomials with respect to the Haar system and show that they form democratic bases in $L^1(0;1).$
Keywords: Haar polynomial, Haar system, democratic bases in $L^1(0; 1)$